Asia as the new master of the business universe (Edited speech of Lord Digby Jones) - Musa, G.; Thirumoorthy, T. (2011)
The global power has shifted from the West to the East. Currently, the main assets or investments for the future should be on education and value added skills, and universities must be well equipped to produce graduates with these qualities. Asia must rise to the current challenge to be leader of the world’s economy and take advantage of three main pillars of globalisation: the movement of ‘product and services’, ‘money’, and ‘people’. In Asia, two notable aspects which hinder the full potential of globalization are free trade protective policies and corruption. Despite the obvious future dominance of Asia economically, globalisation efforts should be directed towards achieving worldwide equality in terms of economy and cultural dominance. Asians must be willing to learn and ask questions, all of which benefit themselves, employers and businesses. In the journey to success, one should hold firmly on the integrity and have the willingness to include and guide others to achieve the same goal.